μ3-Chlorido-μ2-chlorido-(μ3-pyrrolidine-1-carbodithioato-κ4S:S,S′:S′)tris[(triethylphosphane-κP)copper(I)]: crystal structure and Hirshfeld surface analysis - Yi Jiun Tan (Acta Crystallographica Section E: Crystallographic Communications, 2017)
The title trinuclear compound, [Cu3(C5H8NS2)Cl2(C6H15P)3], has the dithiocarbamate ligand symmetrically chelating one CuI atom and each of the S atoms bridging to another CuI atom. Both chloride ligands are bridging, one being μ3- and the other μ2-bridging. Each Et3P ligand occupies a terminal position. Two of the CuI atoms exist within Cl2PS donor sets and the third is based on a ClPS2 donor set, with each coordination geometry based on a distorted tetrahedron. The constituents defining the core of the molecule, i.e. Cu3Cl2S2, occupy seven corners of a distorted cube. In the crystal, linear supramolecular chains along the c axis are formed via phosphane–methylene-C—H...Cl and pyrrolidine–methylene-C—H...π(chelate) interactions, and these chains pack without directional interactions between them. An analysis of the Hirshfeld surface points to the predominance of H atoms at the surface, i.e. contributing 86.6% to the surface, and also highlights the presence of C—H...π(chelate) interactions.